Macrophage migration inhibitory factor‐CD74 interaction regulates the expression of programmed cell death ligand 1 in melanoma cells. Issue 7 (29th May 2019) - Imaoka, Masako; Tanese, Keiji; Masugi, Yohei; Hayashi, Mutsumi; Sakamoto, Michiie
Abstract: Expression of programmed cell death ligand 1 (PD‐L1) on tumor cells contributes to cancer immune evasion by interacting with programmed cell death 1 on immune cells. γ‐Interferon (IFN‐γ) has been reported as a key extrinsic stimulator of PD‐L1 expression, yet its mechanism of expression is poorly understood. This study analyzed the role of CD74 and its ligand macrophage migration inhibitory factor (MIF) on PD‐L1 expression, by immunohistochemical analysis of melanoma tissue samples and in vitro analyses of melanoma cell lines treated with IFN‐γ and inhibitors of the MIF‐CD74 interaction. Immunohistochemical analyses of 97 melanoma tissue samples showed significant correlations between CD74 and the expression status of PD‐L1 ( P  <   .01). In vitro analysis of 2 melanoma cell lines, which are known to secrete MIF constitutively and express cell surface CD74 following IFN‐γ stimulation, showed upregulation of PD‐L1 levels by IFN‐γ stimulation. This was suppressed by further treatment with the MIF‐CD74 interaction inhibitor, 4‐iodo‐6‐phenylpyrimidine. In the analysis of melanoma cell line WM1361A, which constitutively expresses PD‐L1, CD74, and MIF in its non‐treated state, treatment with 4‐iodo‐6‐phenylpyrimidine and transfection of siRNAs targeting MIF and CD74 significantly suppressed the expression of PD‐L1. Together, the results indicated that MIF‐CD74 interaction directly regulated the expression of PD‐L1 and helps tumor cells escape from antitumorigenic immune responses. In conclusion, the MIF‐CD74 interaction could be a therapeutic target in the treatment of melanoma patients. Abstract : This study analyzed the role of CD74 and its ligand macrophage migration inhibitory factor (MIF) on programmed cell death ligand 1 (PD‐L1) expression, by immunohistochemical analysis of melanoma tissue samples and in vitro analyses of melanoma cell lines treated with γ‐interferon and inhibitors of the MIF‐CD74 interaction. The results indicated that MIF‐CD74 interaction directly regulated the expression of PD‐L1.